Design of a Multisensing Control System - A. Osman, Abdalla; J. Alzu baidi, Abdulrasoul; M. Abdelrahman, Ali (Gezira Journal of Engineering and Applied Sciences, 2009)
The  goal   of   this  paper  is  to design  a reconfigurable multisensing  control system. The implemented design tools are based on static random access memory field programmable grid array  (SRAM FPGA)  circuit  board  and  a  very  high speed integrated circuit hardware description language (VHDL). The design steps  start with software development which consists of HDL  processes   where V HDL  program  that  describes  the architectural  behavior  of  the  multisensing  control system. An HDL synthesis is the second step, which converts the design in behavioral description file into gates. These steps are followed by implementation techniques and downloading the design from PC onto FPGA via a joint test action group (J TAG) cable. Different type   of   sensors; namely two ultrasonic, smoke detector, water level switch, thermostat, and light detector are connected to the inputs of the programmed FPGA and activated to test the design. The  results show that  the overall average delay timing between inputs to outputs is equal to 6.437 ns which is relatively small as compared with delay time at sensors and 1/0 modules. Therefore, it can be  clearly  stated  that the speed of  control  is limited by sensors  and 1/0  modules  rather  than  the processing performance of  the proposed design. This  is a  stark  contrast  to  traditional control  system  where  the  processing performance is typically the limiting factor. Thus  the use of  FPGA and V HDL to deploy multi sensing   control   system   efficiently  improves   its  reliability, flexibility, and  real  time  data  processing.  Finally,  it  can  be concluded  that the proposed multisensing control system can be effectively implemented in so many application areas including building security, home automation, robot activities, airports and industry control systems.